Memory trace in feeding neural circuitry underlying conditioned taste aversion in Lymnaea. - Etsuro Ito (Public Library of Science (PLoS), 2012)
Background The pond snail Lymnaea stagnalis can maintain a conditioned taste aversion (CTA) as a long-term memory. Previous studies have shown that the inhibitory postsynaptic potential (IPSP) evoked in the neuron 1 medial (N1M) cell by activation of the cerebral giant cell (CGC) in taste aversion-trained snails was larger and lasted longer than that in control snails. The N1M cell is one of the interneurons in the feeding central pattern generator (CPG), and the CGC is a key regulatory neuron for the feeding CPG. Methodology/principle findings Previous studies have suggested that the neural circuit between the CGC and the N1M cell consists of two synaptic connections: (1) the excitatory connection from the CGC to the neuron 3 tonic (N3t) cell and (2) the inhibitory connection from the N3t cell to the N1M cell. However, because the N3t cell is too small to access consistently by electrophysiological methods, in the present study the synaptic inputs from the CGC to the N3t cell and those from the N3t cell to the N1M cell were monitored as the monosynaptic excitatory postsynaptic potential (EPSP) recorded in the large B1 and B3 motor neurons, respectively. The evoked monosynaptic EPSPs of the B1 motor neurons in the brains isolated from the taste aversion-trained snails were identical to those in the control snails, whereas the spontaneous monosynaptic EPSPs of the B3 motor neurons were significantly enlarged. Conclusion/significance These results suggest that, after taste aversion training, the monosynaptic inputs from the N3t cell to the following neurons including the N1M cell are specifically facilitated. That is, one of the memory traces for taste aversion remains as an increase in neurotransmitter released from the N3t cell. We thus conclude that the N3t cell suppresses the N1M cell in the feeding CPG, in response to the conditioned stimulus in Lymnaea CTA.